Episodios depresivos moderado y su incidencia en las relaciones intrafamiliares de una adolescente de 17 años del tercero de bachillerato de la Unidad Educativa Quevedo - Pilozo Intriago, Luis Fernando (2021)
The present case study was developed with the purpose of determining the incidence of moderate depressive episodes in the interfamiliar relationships of a 17 years old student of the third year of high school of the Unidad educativa Quevedo and in this way be able to elaborate a quialitative investigation of the depressive symptoms such as sadness, discourangement, concentración problems, irritability, guilt, among others wich we Will know how the cause interruptiones in family coexistence. In addition, relevant information was also sought through Clinical interview sessions, were depressive behaviors, thoughts and behaviors were evidenced, depressive thoughts and behaviors were evidenced and also family interview was conducted to determine the state of family relationships within the family context and to determine the posible incidences of moderate depressive episodes in intrafamily relationships within the family. Test for the evaluation of the intrafamilial relations that resulted of Benefit for the respective investigation and the obtaning of important data for the investigation that Will allow the elaboration of a psychotherapeutic scheme for the improvement of the patient as for it’s pathology and it’s intrafamilial relations this investigative Word also counss on updated information bibliografic.